Morphological and physical fitness profile of young female sprint kayakers - López-Plaza, D.; Alacid, F.; Rubio, J. Á.; López-Miñarro, P. Á.; Muyor, J. M.; Manonelles, P. (The Journal of Strength and Conditioning Research, 2019)
Traditionally, physical and anthropometrical profiles of the most successful kayak athletes have been identified in male kayakers. This study attempted to identify the differences in morphology and fitness level of 2 performance-based groups of young elite female paddlers. Eighty-six female kayakers, aged 13.62 ± 0.57 years (mean ± SD), were allocated in 2 groups (Top-10 and Rest) depending on their ranking in the 3 Olympic distances (200, 500, and 1,000 m). All subjects underwent a battery of anthropometrical (heights, mass, girths, and sum of skinfolds), physical fitness (overhead medicine ball throw, countermovement jump, sit-and-reach test, and 20-m multistage shuttle run test), and specific performance assessments (200, 500, and 1,000 m). Best paddlers presented significantly greater anthropometrical values in muscle mass percentage, maturity status, and chronological age (p = 0.05), whereas physical fitness comparison only revealed significant differences in countermovement jump (p = 0.05). Furthermore, aerobic power and muscle mass percentage seem to be crucial in achieving optimal performances at long (1,000 m) and short duration races (200 and 500 m). These findings confirm the importance of a larger and compact morphology, as well as superior fitness level, for success in female kayakers. The current results not only identify the weak areas on body composition and physical fitness depending on the maturity status but also the development of specific training programs for females.